Comprehensive Evaluation of Driver's Propensity Based on Evidence Theory - Jinglei Zhang; Xiaoyuan Wang; Song Gao; Yiqing Song (Discrete Dynamics in Nature and Society)
Traffic safety is related closely with driver’s physiological and psychological characteristics. And the influence on traffic safety is represented as driver’s propensity. Evidence theory is introduced to the evaluation system of driver’s propensity in this paper, and it is utilized to combine the expert opinions, which can eliminate unavoidable uncertain elements in the traditional appraisal methods. The appraisal problems of subjective index can also be resolved by this method in the appraisal system. Results show that the method is objective and reasonable, and driver’s propensity can be evaluated effectively.